ANALISIS PENCAPAIAN KOMPETENSI KOGNITIF PADA MATERI HUKUM DASAR KIMIA MELALUI TWO-TIER TEST - Ita Asfuriyah; Sri Haryani; Harjito Harjito (Universitas Muhammadiyah Semarang, 2017)
This research is a descriptive research that aims to know the achievement of students' cognitive competence on the basic concept of chemistry. The research was conducted in SMA Negeri 1 Kendal with the subject of research as many as 32 students of class X. Research is done through written test by using two-tier multiple choice diagnostic test. The research instrument used 17 items of choice two-tier test. In the data collection, students are asked to answer at the first level as well as the second level of reason. The results showed that the level of achievement of competency indicator that can be achieved by the students on basic chemistry law materials are (1) identification of concept of conservation of mass of 34.4%; (2) microscopic representation of the reaction equation 3.1%; (3) comparative law remains 39.6%; (4) the law of multiples of 26.0%; (5) comparative law of volume of 27.1%; (6) avogadro law 41.7%. Basic competence on basic chemical law material in Class X has not been able to be achieved by students. The achievement level of cognitive competence of grade X students is 28.6% on average and includes less criteria.Keywords: indicators of competence achievement, cognitive competence, two-tiermultiple choice diagnostic test.